Patterns of smartphone usage associated with depressive symptoms in nursing students - Yang, Yajuan; Granlund, Mats; Tao, Fangbiao; Tao, Shuman; Zou, Liwei; Wu, Xiaoyan; Hong, Jingfang; Enskär, Karin (Frontiers in Psychiatry, 2023)
Rather than focusing on the activities that the smartphone has been used for, the existing literature frequently focuses on the association between problematic use of smartphone independent of content of use(self-reported) and depressive symptoms in youth. This study aims to explore patterns of smartphone usage and the association with depressive symptoms in nursing students. This cross-sectional study of nursing freshman(n=1716) was conducted between October and November 2018. Participants were recruited at from three Chinese public medical universities using stratified cluster sampling. Self-rated frequency of 12 different smartphone activities over the preceding week was evaluated. Depressive symptoms were assessed by using the Patient Health Questionnaire (PHQ-9). Of the 1716 students recruited, 1 424 (83.0%)were girls and the mean [SD] age was 18.90 [1.39] years. Using principal component analysis (PCA), two typical usage patterns were indicated. The ‘entertainment pattern’ factor included a high frequency of streaming images or videos, searching information, chatting online, online shopping, downloading, reading online, checking social media sites, taking pictures or videos and playing games. The ‘communication pattern’ had a high frequency of E-mailing, texting and calling. Using logistic regression models, the association between smartphone usage pattern and depressive symptoms was tested. The ‘communication pattern’ was significantly associated with a 53% increase in the odds of moderate and above depressive symptoms (AOR = 1.529; 95%CI = 1.286 - 1.818; p < 0.001), controlling for a set of socio-demographic and smartphone use covariates. This study provides insights into how the patterns of smartphone usage is associated with severity of depressive symptoms in nursing students. It indicates that it primarily may be how we use our smartphones rather than how much we use them, that poses a risk for depression.